Unternehmenszusammenschlüsse von Supermärkten - eine wettbewerbspolitische Analyse am Beispiel von Edeka und Kaiser's Tengelmann - Erdogan, Yeliz

Zum Potenzial von Kryptowährungen. Eine ökonomische Analyse zu den Chancen und Risiken digitaler Währungen - Perampalam, Abirame

Mergers on digital markets - An economic analysis - Nassar, Hamza

Steuerreformen: Investitionsstimulus oder bloß heiße Luft? Wann steuerliche Verlustrückträge der Wirtschaft helfen können - Sureth-Sloane, Caren

Monopolbildung im Zuge der Globalisierung und Digitalisierung der GAFA-Unternehmen (Google, Amazon, Facebook, Apple) - eine wettbewerbspolitische Analyse - Sarsar, Abdelmajid

Kartelle und technischen Absprachen zur Forschung und Entwicklung - Eine wettbewerbspolitische Analyse anhand der Automobilindustrie - Bas, Mikail

Blockchain Technology and the Internet of Thing-Risks and Chances for Supply Chains - Vikue, Baribuma Lucy

Die Fusion von Kaiser's Tengelmann und EDEKA - eine wettbewerbspolitische Analyse - Taskin, Ibrahim

Engaging with self-tracking applications: how do users respond to their performance data? - Constantiou, Ioanna; Mukkamala, Alivelu; Sjöklint, Mimmi; Trier, Matthias (European Journal of Information Systems)
Keywords: Library and Information Sciences; Information Systems; Self-Tracking; User Behaviour; Discontinuance

Engaging with self-tracking applications: how do users respond to their performance data? - Constantiou, Ioanna; Mukkamala, Alivelu; Sjöklint, Mimmi; Trier, Matthias (European Journal of Information Systems)
Keywords: Library and Information Sciences; Information Systems

The Black Box of Social Commerce Platforms - A Closer Look at Users’ Activities - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Wirtschaftsinformatik 2022 Proceedings)

Income Shifting and Management Incentives - Ortmann, Regina; Schindler, Dirk

A Method for Predicting Workarounds in Business Processes - Sven, Weinzierl; Bartelheimer, Christian; Zilker, Sandra; Beverungen, Daniel; Matzner, Martin (Proceedings of the 26th Pacific Asia Conference on Information Systems (PACIS))

Feeless Micropayments and Their Impact on Business Models - Klein, M.; Kundisch, Dennis; Stummer, C. (Handbuch Digitalisierung)

Tax Misperception and Its Effects on Decision Making - Literature Review and Behavioral Taxpayer Response Model - Blaufus, Kay; Chirvi, Malte; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (European Accounting Review)
Previous accounting research shows that taxes affect decision making by individuals and firms. Most studies assume that agents have an accurate perception regarding their tax burden. However, there is a growing body of literature analyzing whether taxes are indeed perceived correctly. We review 128 studies on the measurement of tax misperception and its behavioral implications. The review reveals that many taxpayers have substantial tax misperceptions that lead to biased decision making. We develop a Behavioral Taxpayer Response Model on the impact of provided tax information on tax perception. Besides individual traits, characteristics of the tax information and the decision environment determine the extent of tax misperception. We discuss opportunities for future research and methodological limitations. While there is much evidence on tax misperception at the individual level, we hardly find any research at the firm level. Little is known about the real effects of managers’ tax misperception and on how tax information is strategically managed to impact stakeholders. This research gap is surprising as a large part of the accounting literature analyzes decision making and disclosure of firms. We recommend a mixed-method approach combining experiments, surveys, and archival data analyses to improve the knowledge on tax misperception and its consequences.

Marktmissbrauch in Online-Märkten und die Herausforderungen für die Wettbewerbsbehörden - eine wettbewerbspolitische Betrachtung - Dubbert, Annika

Zur Bekämpfung von Marktmachtmissbrauch in digitalen Märkten – Wettbewerbspolitische Maßnahmen im Vergleich - Miftari, Ardita

Of the efficacy of competition law in dealing with challenges of digital markets - Selected cases of Facebook - Minhaj, Noor

On the Efficacy of EU Competition Policy in the Context of Big Data - Rayhan, Md. Sashi

On the privatization of hospitals - The case of Germany - Busch, Anna Lisa

Towards a Reliable & Transparent Approach to Data-Driven Brand Valuation - Caron, Matthew; Bartelheimer, Christian; Müller, Oliver (Proceeding of the 28th Americas Conference on Information Systems (AMCIS))
Now accounting for more than 80% of a firm's worth, brands have become essential assets for modern organizations. However, methods and techniques for the monetary valuation of brands are still under-researched. Hence, the objective of this study is to evaluate the utility of explanatory statistical models and machine learning approaches for explaining and predicting brand value. Drawing upon the case of the most valuable English football brands during the 2016/17 to 2020/21 seasons, we demonstrate how to operationalize Aaker's (1991) theoretical brand equity framework to collect meaningful qualitative and quantitative feature sets. Our explanatory models can explain up to 77% of the variation in brand valuations across all clubs and seasons, while our predictive approach can predict out-of-sample observations with a mean absolute percentage error (MAPE) of 14%. Future research can build upon our results to develop domain-specific brand valuation methods while enabling managers to make better-informed investment decisions.

Der Marktplatz von Amazon - Eine wettbewerbspolitische Analyse - Kuzuoglu, Muhammed Numan

Zu den Auswirkungen von Big Data auf personalisierte Angebote in digitalen Märkten - eine wettbewerbspolitische Analyse - Sowinski, Olivia

Zu den Vor- und Nachteilen von Luftfahrtallianzen - Eine wettbewerbspolitische Perspektive auf den Alleingang von Emirates - Schmidt, Thomas

An Economic Analysis of Mergers and Aquisitions - The case of Facebook and WhatsApp - Yeboah, Amoabeng

Zu Online-Vergleichsportalen und deren Auswirkungen auf den Markt - Eine wettbewerbspolitische Analyse - Hensel, Jason

The “black box” of social commerce platforms-a closer look at users’ activities - Meydani, Elnaz; Düsing, Christoph; Fedrau, Annamaria; Trier, Matthias

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Manipulation durch Fake-Bewertungen: Einfluss von Such- und Erfahrungsgütern auf das manipulative Verhalten des Verkäufers - N., N.

An Analysis of Coalition Formation Methods to achieve Maximum Social Surplus - N., N.

Die Möglichkeiten der Blockchain-Technologie im Supply Chain Management - eine spieltheoretische Analyse - N., N.

Kindergarten Allocation and the Tradeoff between Stability and Diversity Considerations - N., N.

Effect of the Agent's bargaining positions in the efficiency of matching markets - N., N.

Stabile Zuordnung mit Paaren - Der neue NRMP Algorithmus - N., N.

School choice with reserves and quotas - N., N.

Organisation von Zeitbörsen - N., N.

Wage Bargaining and Employment Revisited: Separability and Efficiency in Collective Bargaining - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya (Scandinavian Journal of Economics)
We analyse the two-dimensional Nash bargaining solution (NBS) by deploying the standard labour market negotiations model of McDonald and Solow (1981). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems, such that the two solutions together replicate the solution of the two-dimensional problem if the NBS is applied. The axiom of Independence of Irrelevant Alternatives is shown to be crucial for this type of decomposability. This result has significant implications for actual negotiations because it allows for the decomposition of a multi-dimensional bargaining problem into one-dimensional problems---and thus helps to facilitate real-world negotiations.
Keywords: Labour market negotiations; efficient bargains; Nash bargaining solution; sequential bargaining; restricted bargaining games

Pay for Tax Certainty? Advance Tax Rulings for Risky Investment under Multi-Dimensional Tax Uncertainty - Chen, An; Hieber, Peter; Sureth-Sloane, Caren

How Do Tax Technology and Controversy Expertise Affect Tax Disputes? - Dyck, Daniel; Lorenz, Johannes; Sureth-Sloane, Caren

Alte Fotografien, neue Erkenntnisse - Liszt-Rohlf, Verena; Wochnik, Markus; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Late-Career Unemployment and Cognitive Abilities - Freise, Diana; Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)
We study the effect of unemployment on cognitive abilities among individuals aged between 50 and 65 in Europe. To this end, we exploit plant closures and use flexible event-study estimations together with an experimentally elicited measure of fluid intelligence, namely word recall. We find that, within a time period of around eight years after the event of unemployment, cognitive abilities only deteriorate marginally — the effects are insignificant both in statistical and economic terms. We do, however, find significant effects of late-career unemployment on the likelihood to leave the labor force, and short-term effects on mental health problems such as depression and sleep problems.

Marginal College Wage Premium under Selection into Employment - Westphal, Matthias; Kamhöfer, Daniel A.; Schmitz, Hendrik (Economic Journal)

Labor market spillover effects of a compulsory schooling reform in Germany - Schiele, Valentin
Compulsory schooling reforms are often used to estimate monetary returns to education. Such reforms are unrelated to individual characteristics and preferences and thus arguably able to eliminate selection bias. However, as these reforms affect a large number of individuals in the relevant age groups, they might have spillover effects on individuals not directly affected by the reform. Such spillover effects constitute a problem for identification and estimation of returns to schooling. As they are difficult to address, they are mostly ignored in the empirical literature. I show that the introduction of the compulsory ninth grade in Germany led to a labor supply shock that might have increased wages and employment of individuals who were not directly subject to the reform and were assumed not to be affected in previous research. To investigate in this kinds of spillover effects, I exploit the staggered introduction of the compulsory ninth grade across German federal states in a difference-in-differences approach. Based on large scale register and survey data, I find no evidence for persistent spillover effects for men. For women, however, my results suggest that the labor supply shock resulting from the reform may have led to a persistent increase in employment and wages.
Keywords: Compulsory schooling; Education; Spillover effects; Cohort size; Wages; Employment

Strategic emphasis on service-based business models during the corona crisis: Are customer solutions a curse or blessing for manufacturing firms? - Akalan, R.; Eggert, A.; Böhm, Eva (Journal of Service Management Research)

Digital technology usage as a driver of servitization paths in manufacturing industries - Eggert, A.; Harrmann, L.; Böhm, Eva (EMAC Annual Conference, Budapest, Hungary)

Should manufacturers publish online reviews in their own online shops? - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Budapest, Hungary)

Servitization in the manufacturing industry: Where do we stand? Where do we come from? - Akalan, R.; Böhm, Eva; Eggert, A. (Journal of Service Management Research)

A Rollercoaster of Emotions – A Semantic Analysis of Fundraising Campaigns over the Course of the COVID-19 Pandemic - Grieger, Nicole; Seutter, Janina; Kundisch, Dennis (Proceedings of the 28th Americas Conference on Information Systems (AMCIS))

Peer-To-Peer Rentals, Regulatory Policies, And Hosts’ Cost Pass-Throughs - Müller, Michelle; Neumann, Jürgen; Kundisch, Dennis (Journal of Management Information Systems)

The ambivalent role of monetary sales incentives in service innovation selling - Alavi, Sascha; Böhm, Eva; Habel, Johannes; Wieseke, Jan; Schmitz, Christian; Brüggemann, Felix (Journal of Product Innovation Management)
Keywords: Management of Technology and Innovation; Strategy and Management

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric generalized autoregressive conditional heteroscedasticity (GARCH) models with long memory are introduced. A multiplicative decomposition of the volatility into a conditional component and an unconditional component is assumed. The estimation of the latter is carried out by means of a data-driven local polynomial smoother. According to the revised recommendations by the Basel Committee on Banking Supervision to measure market risk in the banks’ trading books, these new semiparametric GARCH models are applied to obtain rolling one-step ahead forecasts for the value-at-risk and expected shortfall (ES) for market risk assets. Standard regulatory traffic-light tests and a newly introduced traffic-light test for the ES are carried out for all models. In addition, model performance is assessed via a recently introduced model selection criterion. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long-memory GARCH models are a meaningful substitute for their conventional, parametric counterparts.
Keywords: long memory; generalized autoregressive conditional heteroscedasticity (GARCH) models; value-at-risk (VaR); expected shortfall (ES); traffic-light test; backtesting

Erfolgreiches People Management in KMU und Start-ups - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Methodenverliebt am Markt vorbei? - Rebert, Tobias; Tomin, Slawa; Wach, Bernhard; Kabst, Rüdiger (Intrapreneurship)

Erkenntnisse aus Arbeitgeberbewertungen – Potenzial von Atmosphäre und Arbeitsplätzen. - Radermacher, Katharina; Herdejürgen, Enja Marie (PERSONALquarterly)

Long‐term effects of institutional conditions on perceived corruption – A study on organizational imprinting in post‐communist countries - Auer, Thorsten Fabian; Knorr, Karin; Thommes, Kirsten (Business Ethics, the Environment & Responsibility)
In this paper, we apply imprinting theory to examine how institutional transformation substantially influences perceptions of corruption that we argue to be incorporated to a varying extent in organizations founded in that period. For this purpose, we compare the effect of a sudden shock (dissolution of the Soviet Union) on the managers' present perceptions to that of a steady transition (EU accession). We consult the 5th round of the Business Environment and Enterprise Performance Survey from 2012 to 2014 analyzing 4715 interviews with managers of organizations from twelve Central and Eastern European countries. Our results reveal striking differences in the present perception of corruption for organizations founded immediately before and immediately after these institutional transitions. The study's results contribute to the research on imprinting theory regarding the relationship between organizations and institutional conditions that constitutes a lasting effect on organizational structures. Thus, applying an institutional perspective that considers less stable periods for organizations yields a promising avenue in research on organizational behavior.
Keywords: Central and Eastern Europe; corruption; imprinting theory; institutional transformation; shock-imprinting

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brünninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun
Manufacturing companies are challenged to make the increasingly complex work processes equally manageable for all employees to prevent an impending loss of competence. In this contribution, an intelligent assistance system is proposed enabling employees to help themselves in the workplace and provide them with competence-related support. This results in increasing the short- and long-term efficiency of problem solving in companies.
Keywords: Assistance system; Knowledge graph; Information retrieval; Neural networks; AR

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brunninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

Determinants of Trust in Smart Technologies - Papenkordt, Jörg; Thommes, Kirsten (Human-Technology Interaction)

Erkenntnisse aus Arbeitgeberbewertungen: Das Potential von Arbeitsatmosphäre und Arbeitsplatzgestaltung für die Weiterempfehlungsbereitschaft (Studie Industrieverband Büro und Arbeitswelt e. V. (IBA).)

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Exploring the customer journey of voice commerce: A research agenda - Böhm, Eva; Eggert, A.; Garnefeld, I.; Holzmüller, H.; Schaefers, T; Steinhoff, Lena; Woisetschläger, D. (Journal of Service Management)

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure

Betriebliche Gesundheitsförderung: Ein leeres Versprechen? - Auer, Thorsten Fabian; Sennefelder, Lisa; Meier, Heiko (Public Health Forum)
Unternehmen investieren zunehmend in Angebote Betrieblicher Gesundheitsförderung (BGF). Dabei stellt sich die Frage nach dem Kosten-Nutzen-Verhältnis jenseits des individuellen Nutzens durch die Förderung der Mitarbeitergesundheit. Deshalb wurden im Rahmen einer Sekundäranalyse Effekte der BGF auf den Unternehmenserfolg berechnet. Die Ergebnisse lassen vermuten, dass sich eine verhaltensorientierte BGF kaum positiv auf die Arbeitsproduktivität und Kommunikationsstruktur in Unternehmen auswirkt.
Keywords: Kommunikation; Arbeitsproduktivität; Betriebliche Gesundheitsförderung; Kosten-Nutzen-Verhältnis

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Entrepreneurship, Green Business - Schneider, Jennifer Nicole

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Creative Thinking - Schneider, Jennifer Nicole

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Canvas Model - Schneider, Jennifer Nicole

EU-CERT. First Transnational Project Meeting. Presentation at the EU-CERT Meeting: Financial, Marketing and Dissemination. - Schneider, Jennifer Nicole

Family Business Library. Presentation at the LTTA of FBL: Motivation, Barriers and Problems while starting a business - Schneider, Jennifer Nicole

Identification of Human and Organizational Key Design Factors for Digital Maturity – A Fuzzy-Set Qualitative Comparative Analysis - Schneider, Martin; Hellweg, Talea Davina; Menzefricke, J. S. (Proceedings of the Design Society)
Abstract This paper examines how human and organizational factors need to be designed to achieve strong technological maturity of either the products or the production process. In a fuzzy-set qualitative comparative analysis (fs/QCA), a combination of intensive training and strong worker participation is found to be associated with strong technological maturity in the two organizational contexts: firms with a strong entrepreneurial culture and in large firms oriented towards customer-oriented innovation. Overall, the paper uncovers designs or causal recipes for a successful digital transformation.

Co-creating business value through IT-business operational alignment in inter-organisational relationships: Empirical evidence from regional networks - Trang, S.; Mandrella, M.; Marrone, M.; Kolbe, L. (European Journal of Information Systems)

What to do after a data breach? Examining apology and compensation as response strategies for health service providers - Masuch, K.; Greve, M.; Trang, S. (Electronic Markets)

Apologize or Justify? Examining the Impact of Data Breach Response Actions on Stock Value of Affected Companies - Masuch, K.; Greve, M.; Trang, S. (Computers & Security)

Smart cities and smart governance models for future cities - Nastjuk, I.; Trang, S.; Papageorgiou, E. (Electronic Markets)

Künstliche Intelligenz in der industriellen Arbeitswelt - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Since Albert and Whetten: the dissemination of Albert and Whetten’s conceptualization of organizational identity - Knorr, Karin; Hein-Pensel, Franziska (Management Review Quarterly)
Abstract Since the seminal work of Albert and Whetten, the organizational identity concept has become ubiquitous and highly relevant in various fields. This study systematically reviews how Albert and Whetten’s concept of organizational identity has been disseminated in different research areas. It employs quantitative (topic modeling) and qualitative text analysis, as well as a network analysis to examine a sample of 1,041 papers published between 1985 and mid-2022 that cite Albert and Whetten’s seminal work. Using this method of systematic literature analysis, the current study investigates the criteria of the basic definition and hypotheses mentioned in their work that contribute to its increasing significance, and those with the potential to become substantial aspects of future organizational identity research. Accordingly, Albert and Whetten’s conceptualization of organizational identity is often partially adopted in the literature. Thus, this study contributes to organizational identity research by unveiling further research questions on the evolving character of organizational identity, research methodology, and quantitative operationalization, on the basis of Albert and Whetten’s organizational identity conceptualization.
Keywords: Strategy and Management; Business; Management and Accounting (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia A.; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Losses Never Sleep - The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning

Lagerkapazitätsdimensionierung als betriebswirtschaftliches Entscheidungsproblem - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Strategische Erfolgsplanung für Produktinnovationen - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Tax Avoidance and Vertical Interlocks within Multinational Enterprises - Giese, Henning; Koch, Reinald; Gamm, Markus

Decision-making under Imperfect Information with Bayesian Learning or Heuristic Rules - Burs, Carina; Gries, Thomas
Information is one of the most important ingredients for decision-making. While the neoclassical assumption of perfect information is surely an important conceptual benchmark for discussing efficient allocations, it is obviously far from describing a rational choice under real conditions. In reality, optimal choices should be considered choices under imperfect information. Thus, decision-makers' information problem can be solved by two strategies. Either they collect an optimal set of information to make an optimal allocation choice under this imperfect information set or they can apply heuristic reasoning. In this paper, we suggest a formal model framework for the example of a simple consumer decision for the allocation of differentiated goods to explore information acquisition strategies in such a simple standard choice situation. Using the model variation under perfect information as a benchmark, we answer the following questions. First and most importantly, under imperfect information, can a heuristic rule substitute information acquisition as an optimal choice? Second, what is the role of risk aversion in the information acquisition process? Finally, we explore the differences to the benchmark, both ex ante the first purchase decision and ex post when repeated purchases and consumption allows for experiences with the choices made.
Keywords: information economics; imperfect information; Bayesian learning; risk; heuristics; differentiated products

The smoots Package in R for Semiparametric Modeling of Trend Stationary Time Series - Feng, Yuanhua; Gries, Thomas; Letmathe, Sebastian; Schulz, Dominik (The R Journal)
Keywords: Statistics; Probability and Uncertainty; Numerical Analysis; Statistics and Probability

Towards a Process Model for Social Media Marketing - Arslan, Kader; Trier, Matthias (Proceedings of the 33rd Australasian Conference on Information Systems (ACIS 2022))
Keywords: Social media; Social media marketing process; Social media strategy; Social media management; Guidelines

Möglichkeiten und Grenzen der Messung, Kontrolle und Sicherung der Qualität logistischer Prozesse - Hrnjadovic, Damir (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Implikationen einer wertorientierten Unternehmensführung für Standortplanungsentscheidungen - Fiedler, Moritz (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Betriebliche Standortplanung international agierender Unternehmen - Osthoff, Lennart (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Kategorisierungsmöglichkeiten für die Erzeugung von Dienstleistungen - Opitz, Oliver (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Entscheidungsunterstützung durch das Controlling mittels Reporting Design - Faupel, Christian (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Aktuelle Fragestellungen zu Produktion, Controlling und Logistik

Process Mining of Knowledge-Intensive Processes: An Action Design Research Study in Manufacturing - Löhr, Bernd; Brennig, Katharina; Bartelheimer, Christian; Beverungen, Daniel; Müller, Oliver (International Conference on Business Process Management)
Existing process mining methods are primarily designed for processes that have reached a high degree of digitalization and standardization. In contrast, the literature has only begun to discuss how process mining can be applied to knowledge-intensive processes—such as product innovation processes—that involve creative activities, require organizational flexibility, depend on single actors’ decision autonomy, and target process-external goals such as customer satisfaction. Due to these differences, existing Process Mining methods cannot be applied out-of-the-box to analyze knowledge-intensive processes. In this paper, we employ Action Design Research (ADR) to design and evaluate a process mining approach for knowledge-intensive processes. More specifically, we draw on the two processes of product innovation and engineer-to-order in manufacturing contexts. We collected data from 27 interviews and conducted 49 workshops to evaluate our IT artifact at different stages in the ADR process. From a theoretical perspective, we contribute five design principles and a conceptual artifact that prescribe how process mining ought to be designed for knowledge-intensive processes in manufacturing. From a managerial perspective, we demonstrate how enacting these principles enables their application in practice.

(How) do advanced data and analyses enable HR analytics success? A neo-configurational analysis - Strohmeier, Stefan; Collet, Julian; Kabst, Rüdiger (Baltic Journal of Management)
Purpose Enabled by increased (“big”) data stocks and advanced (“machine learning”) analyses, the concept of human resource analytics (HRA) is expected to systematically improve decisions in human resource management (HRM). Since so far empirical evidence on this is, however, lacking, the authors' study examines which combinations of data and analyses are employed and which combinations deliver on the promise of improved decision quality. Design/methodology/approach Theoretically, the paper employs a neo-configurational approach for founding and conceptualizing HRA. Methodically, based on a sample of German organizations, two varieties (crisp set and multi-value) of qualitative comparative analysis (QCA) are employed to identify combinations of data and analyses sufficient and necessary for HRA success. Findings The authors' study identifies existing configurations of data and analyses in HRM and uncovers which of these configurations cause improved decision quality. By evidencing that and which combinations of data and analyses conjuncturally cause decision quality, the authors' study provides a first confirmation of HRA success. Research limitations/implications Major limitations refer to the cross-sectional and national sample and the usage of subjective measures. Major implications are the suitability of neo-configurational approaches for future research on HRA, while deeper conceptualizing and researching both the characteristics and outcomes of HRA constitutes a core future task. Originality/value The authors' paper employs an innovative theoretical-methodical approach to explain and analyze conditions that conjuncturally cause decision quality therewith offering much needed empirical evidence on HRA success.
Keywords: Management of Technology and Innovation; Marketing; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management

The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Shortcut Learning in Financial Text Mining: Exposing the Overly Optimistic Performance Estimates of Text Classification Models under Distribution Shift - Caron, Matthew (2022 IEEE International Conference on Big Data (Big Data))
In recent years, many cases of deep neural networks failing dramatically when faced with adversarial or real-world examples have been reported. Such failures, which are quite hard to detect, are often related to a generalization problem known as shortcut learning. Yet, with state-of-the-art transformer models now being ubiquitous in financial text mining, one cannot help but wonder how reliable the results conveyed in the ever-growing literature genuinely are. Against this background, we expose, in this work, how vulnerable contemporary financial text mining approaches are to shortcut learning. Focussing on the common learning task of financial sentiment classification, we assess, using two entity-based sampling strategies and our publicly-available dataset, the discrepancies between i.i.d. and o.o.d. performance estimates of four transformer models. Our results reveal that o.o.d. performance estimates are consistently weaker than those of their i.i.d. counterparts, with the error rate increasing by as much as 29.7%, thus, demonstrating how this issue can, when overlooked, lead to misleading evaluations. Moreover, we show how additional preprocessing steps, such as entity removal and vocabulary filtering, can help reduce the effects of shortcut learning by filtering out entity-related linguistic cues.

Towards Automated Moderation: Enabling Toxic Language Detection with Transfer Learning and Attention-Based Models - Caron, Matthew; Bäumer, Frederik S.; Müller, Oliver (55th Hawaii International Conference on System Sciences (HICSS))
Our world is more connected than ever before. Sadly, however, this highly connected world has made it easier to bully, insult, and propagate hate speech on the cyberspace. Even though researchers and companies alike have started investigating this real-world problem, the question remains as to why users are increasingly being exposed to hate and discrimination online. In fact, the noticeable and persistent increase in harmful language on social media platforms indicates that the situation is, actually, only getting worse. Hence, in this work, we show that contemporary ML methods can help tackle this challenge in an accurate and cost-effective manner. Our experiments demonstrate that a universal approach combining transfer learning methods and state-of-the-art Transformer architectures can trigger the efficient development of toxic language detection models. Consequently, with this universal approach, we provide platform providers with a simplistic approach capable of enabling the automated moderation of user-generated content, and as a result, hope to contribute to making the web a safer place.

Commentaries on Relationship Marketing: The Present and Future of Customer Relationships in Services - Steinhoff, Lena; Palmatier, R. W.; Martin, K. D.; Fox, G.; Henderson, C. M.; Saint Clair, J. K.; Yan, S.; Lee, J.-Y.; Perko, T.; Harmeling, C. M. (Journal of Service Management Research)